Differential Expression of E-Cadherin and High Molecular Weight Cytokeratin in Invasive Lobular and Ductal Breast Carcinoma - Ali S. Sawan (Journal of King Abdulaziz University: Medical Sciences, 2023)
This study included 62 breast biopsy cases; 39 invasive breast carcinoma, 11 non-invasive carcinoma cases and 12 benign breast lesions. Immunohistochemical cases revealed; ductal and mucinous carcinoma, epithelial component in metaplastic carcinoma, and benign breast lesions were positive to E-cadherin. All lobular carcinomas, sarcomatoid component of metaplastic carcinoma and neuroendocrine carcinoma were totally negative to E-cadherin. However, 45.5% of invasive ductal carcinoma, all lobular carcinomas, plus all benign breast lesions showed positive reaction to high molecular weight cytokeratin. Cases of ductal carcinoma in situ were all negative to high molecular weight cytokeratin. Previous results concluded that immunohistochemical study of E-cadherin expression was recommended as a tool to differentiate between challenging cases of lobular and ductal carcinoma lesions as it has no role in differentiating ductal hyperplastic cases from ductal carcinoma in situ. In contrast, high molecular weight cytokeratin has no role in discriminating lobular from ductal carcinoma, thus it can differentiate between ductal hyperplasia and ductal carcinoma in situ.